(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Various studies indicate that Islamic Religious Education (PAI) teaching materials in schools still tend to be oriented towards the cognitive aspects of religion and have not optimally integrated multicultural values, thus potentially hindering the strengthening of students’ moderate character in a pluralistic society. This study aims to analyze the integration of multicultural values ​​in the development of PAI teaching materials and identify challenges to their implementation in inclusive learning. The study used a qualitative approach with a literature study method. Data sources were obtained from 20 national and international scientific articles, reference books, and education policy documents published in the 2020–2025 period. Literature selection was carried out based on criteria of relevance to multicultural education, inclusive education, teaching materials development, and PAI learning. Data were analyzed using content analysis techniques through the stages of identification, categorization, interpretation, and synthesis of findings. The results of the study indicate that the integration of multicultural values ​​in PAI teaching materials is still not optimal. The main obstacles include limited teacher competency, minimal inclusive education training, and a lack of contextual learning resources. This research emphasizes the importance of developing PAI teaching materials that are adaptive, inclusive, and oriented towards strengthening moderate, tolerant characters and respect for diversity in the educational environment.